Penentuan Harga Pokok Produksi Menggunakan Metode Activity Based Costing - Abdul Qodir Umrin; Achmad Ma'arif Ubaidillah Syakur; Achmad Davit Hardianto; Ribangun Bamban Jakaria (Pusat Riset dan Inovasi Nasional, 2024)
Establishing production costs involves combining, grouping, and allocating costs related to acquiring raw materials, labor expenses, and overhead expenses when a company converts raw materials into finished products for sale. However, in the domain of cost accounting, there are certain limitations that remain when determining the base price for manufactured products. For example, PT Currently, they have switched from Traditional Costing Methods to Activity Based Costing (ABC) Approach. This notification approach uncovers the activities involved in the production process of these goods to obtain a more accurate product cost estimate. This calculation includes all costs collected during the production process, including estimates of raw material costs, labor wages and overhead costs. By comparing the calculations between Traditional Costs and Activity Based Costing, the hope is to get a more precise assessment regarding the Cost of Goods Production. This will be a guide for management in making more accurate decisions and cost allocation.